2003
DOI: 10.1097/00008469-200304000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer in Southern India: the influence of body size, diet, infections and sexual practices

Abstract: Between 1996 and 1999, we carried out a study in Southern India on risk factors for oral cancer. The study included 591 incident cases of cancer of the oral cavity (282 women) and 582 hospital controls (290 women). Height was unrelated to oral cancer risk. Body mass index (weight in kilograms/height in metres squared) was inversely associated with risk (P for trend<0.001). Paan chewers with low BMI were at particularly high risk. Risk was increased among subjects consuming meat (odds ratio (OR) 1.54, 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 24 publications
8
71
1
Order By: Relevance
“…General characteristics of case-control and cohort studies are shown in Tables 1 and 2, respectively. Case-control studies were published between 1994 and 2014; three were conducted in Italy (13,19,22) , two each in Iran (10,15) , China (12,23) and Australia (14,29) , and one each in Poland (16) , Spain (11) , Czech Republic (17) , Brazil (18) , UK (20) , India (24) , Hawaii (25) , Mexico (26) , Sweden (27) and Uruguay (28) . One was a multinational study conducted in nine countries worldwide (Italy, Spain, Poland, Northern Ireland, India, Cuba, Canada, Australia and Sudan) (21) Cohort studies were published between 1998 and 2012; nine were conducted in the USA (30,31,(34)(35)(36)(37)39,40,45) and eight were conducted in Europe (32,33,38,(41)(42)(43)(44)46) .…”
Section: Literature Searchmentioning
confidence: 99%
“…General characteristics of case-control and cohort studies are shown in Tables 1 and 2, respectively. Case-control studies were published between 1994 and 2014; three were conducted in Italy (13,19,22) , two each in Iran (10,15) , China (12,23) and Australia (14,29) , and one each in Poland (16) , Spain (11) , Czech Republic (17) , Brazil (18) , UK (20) , India (24) , Hawaii (25) , Mexico (26) , Sweden (27) and Uruguay (28) . One was a multinational study conducted in nine countries worldwide (Italy, Spain, Poland, Northern Ireland, India, Cuba, Canada, Australia and Sudan) (21) Cohort studies were published between 1998 and 2012; nine were conducted in the USA (30,31,(34)(35)(36)(37)39,40,45) and eight were conducted in Europe (32,33,38,(41)(42)(43)(44)46) .…”
Section: Literature Searchmentioning
confidence: 99%
“…Most of the oral cancers in India are linked with diet, weight and other lifestyle factors including betal quid (paan) chewing (Tondon et al, 2000). Body mass index (BMI) has been inversely associated with oral cancer, and paan chewers with low BMI has a very high risk of oral cancer (Rajkumar et al, 2003). Sharma et al (2010) have observed variable incidence of oral cancer within one geographical location as per age, sex, site or habit.…”
Section: Cancer Mouthmentioning
confidence: 99%
“…72,73 In Sweden, several large, population-based, case-control studies reported no association between intensity or duration of moist snuff use (pasteurized and low in TSNA) and oral cancer. 69,[74][75][76] In India, where smokeless tobacco is often mixed with other carcinogenic substances (betel, areca nut, and lime), very strong doseresponse relationships were observed with increased intensity and duration of smokeless tobacco use and risk of premalignant 77,78 and malignant 44,79,80 lesions of the oral cavity. These conflicting findings can be explained by type of smokeless tobacco use, variability in qualitative and quantitative measures of use, and the number of cases and their anatomic site distribution.…”
Section: Smokeless Tobaccomentioning
confidence: 99%